TYPOLOGY OF URGENT REASONS AND CHILD’S BEST INTERESTS IN MARRIAGE DISPENSATION: At Indramayu Religious Court - Aziz, Abd Aziz Tambunan; Abdul Rahman Hamid; Sanusi (Dusturiyah: Jurnal Hukum Islam, Perundang-undangan dan Pranata Sosial, 2026)
Child marriage dispensation remains a crucial issue in Indonesian Islamic family law because it places judges between the legal restriction of minimum marriage age and the social realities faced by families. This article examines urgent reasons and the best interests of the child in marriage dispensation determinations at the Indramayu Religious Court. The study aims to identify the typology of urgent reasons constructed in judicial considerations and to assess the consistency of those considerations with Supreme Court Regulation Number 5 of 2019. This research uses a normative-empirical legal method with statutory, case, and content analysis approaches. The primary data consist of marriage dispensation determinations from the Indramayu Religious Court, supported by relevant regulations, literature, previous studies, and statistical data on dispensation cases. The findings show that urgent reasons are constructed through several patterns: pregnancy, intimate relationships between prospective spouses, fear of zinā and social shame, family approval, and economic readiness of the prospective husband. The study also finds that the implementation of Supreme Court Regulation Number 5 of 2019 is relatively consistent at the formal-procedural level, but still requires substantive strengthening, particularly regarding meaningful child participation, freedom from coercion, education, health, and alternatives to marriage. This article contributes to Islamic family law studies by emphasizing that urgent reasons must be controlled by the principle of the best interests of the child.